State officials in the themes of Opsikion, the Anatolikoi and the Kibyrraiotai: new and recently revisited sigillographic evidence. - KARAGIORGOU, Olga; CHARALAMPAKIS, Pantelis; MALATRAS, Christos (Byzantina Symmeikta, 2016)
The aim of the project entitled “Towards an institutional and social history of Byzantine Asia Minor on the evidence of seals and other sources (7th - 13th centuries)” (abbreviated as SigCorpByzAMthemes; project’s code 4492) was to look afresh at the institutional and social history of Byzantine Asia Minor using as main research tool reliable and well-dated prosopographic lists of all the state officials once active in the three earliest Asia Minor themes: the Opsikion, the Anatolikoi and the Kibyrraiotai. The compilation of these prosopographic lists was based mostly, as was to be expected, on sigillographic evidence, duly complemented by relevant references in literary and other non-sigillographic sources.